2014
DOI: 10.1002/jcu.22185
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal ultrasound‐guided injection of methotrexate in the treatment of ectopic interstitial pregnancies

Abstract: The successful outcome in our patients suggests that the transabdominal route is feasible and safe as a nonsurgical option for terminating an ectopic interstitial pregnancy in patients in whom the transvaginal route is contraindicated or difficult, provided the patients are properly selected and operators have sufficient experience with the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, low-dose MTX treatment has been shown to have no effect on coexisting IUP [ 29 ]. The ultrasound-guided local injection of 25 mg MTX has been reported to terminate IPs without affecting IUPs [ 54 , 55 ]. Studies have also proved that MTX doses within the range of 12.5–30 mg will not affect the growth and intelligence of infants [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, low-dose MTX treatment has been shown to have no effect on coexisting IUP [ 29 ]. The ultrasound-guided local injection of 25 mg MTX has been reported to terminate IPs without affecting IUPs [ 54 , 55 ]. Studies have also proved that MTX doses within the range of 12.5–30 mg will not affect the growth and intelligence of infants [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [ 56 ] reported seven cases of suspected HP with an EP mass less than 4 cm in length, and they achieved good outcomes after expectant treatment. Certainly, there are other reports of IUP miscarriage (1/3) [ 55 ]. However, based on the current limited clinical research [ 57 , 58 , 59 ], the survival rate of IUP with this treatment remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…So far, MTX is frequently applied as a gold non‐surgical medication for ectopic pregnancy . It was reported that 25 mg MTX local injection into the ectopic sac or embryo was effective for ectopic interstitial pregnancies . However, during heterotopic interstitial pregnancy, the MTX injection becomes controversial because of its fetal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…19 It was reported that 25 mg MTX local injection into the ectopic sac or embryo was effective for ectopic interstitial pregnancies. 20 However, during heterotopic interstitial pregnancy, the MTX injection becomes controversial because of its fetal toxicity. The US Food and Drug Administration labeled MTX contraindicated during pregnancy and lactation.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to inject methotrexate directly into the gestational sac was for the purpose of increasing the success of local treatment. A retrospective survey of direct methotrexate injection into the gestational sac under ultrasound visualization in 14 hemodynamically stable patients with interstitial pregnancy showed that this technique is an effective alternative to surgery [25]. Here 1 mL of fluid was aspirated from the gestational sac and 1 mL of methotrexate solution was injected, to avoid sac overdistension and decrease the risk of interstitial rupture.…”
Section: Discussionmentioning
confidence: 99%